147k views
1 vote
Please help!
what is the simplest form of the expression sqrt 2-sqrt 10/sqrt 2+sqrt 10

2 Answers

3 votes

Answer:


(1)/(2)(√(5)-3)

Explanation:

Given expression,


(√(2)-√(10))/(√(2)+√(10))

By rationalising the denominator,


=(√(2)-√(10))/(√(2)+√(10))*(√(2)-√(10))/(√(2)-√(10))


=((√(2)-√(10))^2)/((√(2))^2-(√(10))^2)

( ∵ ( a + b ) ( a - b ) = a² - b² )


=((√(2)-√(10))^2)/(2-10)


=(2+10-2√(20))/(-8)

( ∵ (a + b)² = a² + 2ab + b² )


=-(1)/(8)(12-4√(5))


=-(1)/(2)(3-√(5))


=(1)/(2)(√(5)-3)

User Psyrendust
by
5.5k points
3 votes

Answer:


√(2)-√(5)+√(10)

Explanation:

we have


√(2)-(√(10))/(√(2)) +√(10)

we know that


√(10)=√(2)*√(5)

substitute


√(2)-(√(2)*√(5))/(√(2)) +√(10)

simplify


√(2)-√(5)+√(10)

User Manoj De Mel
by
5.6k points